Carbohydrate-protein ingestion improves subsequent running capacity towards the end of a football-specific intermittent exercise - Alghannam, A. F. (Applied Physiology, Nutrition, and Metabolism, 2011)
The majority of football players succumb to fatigue towards the end of the game. This study was designed to examine the influence of protein coingestion with carbohydrate (CHO) vs. an isocaloric CHO supplement on subsequent running capacity towards the end of a simulated football match. Six male amateur football players participated in 3 trials applied in a randomized cross-over experimental design. A laboratory-based, football-specific intermittent exercise was allocated for 75 min interspersed with a 15-min recovery, immediately followed by run time to fatigue (RTF) at 80% peak oxygen consumption. In each trial, prior to exercise and during half-time, participants randomly ingested a placebo (PLC), 6.9% CHO, or 4.8% CHO plus 2.1% protein (CHO-P) supplements matched for color and taste. CHO-P resulted in longer RTF (23.02 ± 5.27 min) than did CHO (16.49 ± 3.25 min) and PLC (11.00 ± 2.80 min) (p < 0.05). Blood glucose was higher in CHO-P at the point of fatigue (4.68 ± 0.64) compared with CHO and PLC (3.92 ± 0.29 and 3.66 ± 0.36, respectively; p < 0.05). Ratings of perceived exertion were lower in the CHO-P subjects at the onset of exercise and towards the end of intermittent exercise when compared with the PLC and CHO subjects (p < 0.05). When protein was added to a CHO supplement, subsequent running capacity following limited recovery from intermittent exercise was enhanced. This improvement suggests that protein coingestion may exert an ergogenic benefit upon endurance capacity during intermittent activity.